Identifikasi Potensi Korupsi Barang Sitaan - Raynal Yasni (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: This paper aims to identify various potentials and loopholes for misappropriation of confiscated goods that lead to corrupt acts based on several valid literature and social media sources. I also analyse a reliable control model for the management of confiscated goods that can be applied within the confiscated goods management institution. Method: The method used is a qualitative approach using secondary data in the form of news documentation, regulations, and social media as well as literature review. The author also uses primary data from direct field observations and interviews with related respondent who has had direct experience of the confiscation of goods by officials to strengthen arguments. Result: The results show that three basic weaknesses in the management of confiscated goods occur in the aspects of control, systems, and moral hazard. Only few numbers of confiscation management offices investigated may limit the generalization of the results, in addition to the need for further evidence to strengthen qualitative aspect and the secondary data used. Limitation: The discussion to confiscated goods when they are still being managed or stored by law enforcement institution and Rupbasan and have not yet been executed based on a permanent court decision to be sold or auctioned Contribution: It is hoped that the results of this study can be used as a reference for government agencies dealing with fiscal policy and law enforcement to make improvements, especially in terms of taking a more serious look at the potential for corruption from the mismanagement of goods.